Study of prevalence and epidemiological variables of the hiv infection in pregnant women attended in clinical Hospital’s Maternity from Curitiba - Sbalqueiro, Renato Luiz; Reggiani, Claudete; Tristão, Edson Gomes; Urbanetz, Almir Antonio; Andrade, Rosires Pereira de; Nascimento, Denis José; Carvalho, Newton Sergio de (Brazilian Journal of Sexually Transmitted Diseases, 2004)
Introduction: The infection with the HIV virus is a worldwide concern, afflicting patients during their reproductive life. One of a many conse-quences is the vertical transmission of the HIV virus. Objective:the object of this research is to determine the prevalence of HIV positive patientsattending the prenatal clinics at the Universidade Federal do Paraná, during the period of June 1997 through March 1998. Methods: we tested 436patients which have made the anti-HIV test. Results:we found 9 patients tested positive for a 2% total. But of those, 7 patients were originallyreferred to the clinics due to a positive HIV status. Excluding those, the incidence dropped to 0,4%. A questionnaire was submitted that includednumber of sexual partners, historical STD, historical of blood transfusions or of drug abuse by either her or her sexual partner, also history of homo-sexual activity by her sexual partner. The data was tabulated base on serologic status as well as socio-demographic information obtained from thequestionnaire. We analyzed the data using the qui-square test, with a level of significance of p <or = 0,05. Conclusion: significant correlation wasfound between a positive HIV status and a history of drug addiction by either partner, history of STD and homosexual activity by patient’s sexual partners and those HIV positive.